SEJARAH PENDIDIKAN POLITIK UMAT ISLAM MENUJU INDONESIA YANG IDEAL - Abu Haif (Universitas Islam Negeri Alauddin Makassar, 2013)
To build political culture in Indonesia is not easily as we say. It needs much time, thoughts and sacrifices. The idel democracy as one of requirements to make the clean governance is always discussed in various chance. Islam elites usually refer to “the glory of the past” wich was ever practiced by Great Prophet Muhammad (puh) when he ruled Madinah State. However, in the present day, the ideal democratic governance in Indonesia is so difficult to implement. It is because thee system society and governance style are rather different than it was in the time of Madinah. Political culture in Indonesia, vertically or horizontally is not so condusive. But, Moslems in Indonesia must make efforts to always do the best.